Alice in Borderland. Volume 8 - Aso, Haro, 1980-; Luka M. (Viz signature., 2023)
An action-packed thriller and source of the hit Netflix drama where the only way to survive is to play the game! Eighteen-year-old Ryohei Arisu is sick of his life. School sucks, his love life is a joke, and his future weighs on him like impending doom. As he struggles to exist in a world that can't be bothered with him, Ryohei feels like everything would be better if he were anywhere else. When a strange fireworks show transports him and his friends to a parallel world, Ryohei thinks all his wishes have come true. But this new world isn't an empty paradise, it's a vicious game. And the only way to survive is to play. Not every visitor to Borderland spends their time struggling to survive. Much like Arisu, some are hunting for the truth behind the strange and deadly world they've landed in. But whether that means searching for the boundaries of their strange prison or finding ways to expose Borderland to the media back home, does the truth even matter if everyone dies before they can share it?